Teachers' Perception of Online Learning in The Pandemic Era - Fergina Lengkoan; Paula Audry Rombepajung (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
The Covid-19 pandemic situation has changed many aspects of life, including the learning process. In this regard, researchers are interested in analyzing teachers' perceptions of online learning. This study explains teachers' opinions about online learning and its impact, such as the disadvantages, advantages, and difficulties of online learning during the pandemic. This study uses qualitative research using questionnaires through a google form. The resource persons in this study were English teachers in North Sulawesi, totaling ten teachers. The main target of this research is the teacher's perception because they have experience in online learning in a pandemic situation. From the research data, 90% of teachers choose face-to-face in the learning process because they cannot interact directly with students and experience difficulties in the learning process due to internet access problems. Although online learning has many difficulties and weaknesses, there is no choice but to stop the spread of COVID-19. We must continue to study online. Here teachers and students are equally challenged in creative and active online learning methods and objects. One of the most important is the stability of the internet network, then adequate devices or computers, applications with accessible platforms, and online socialization that carry out efficiently, effectively, sustainably, and integrative to all interested parties in the field of education.